Chronic Dysuria Following Ginger (Zingiber officinale) Use: A Case Report: - Jaladat, Amir Mohammad; Akbarzadeh, Elham; Heydari, Mojtaba; Atarzadeh, Fatemeh (Galen Medical Journal, 2018)
Background: Although ginger is considered a harmless remedial substance for a wide range of medical complaints, according to Persian medicinal texts, its long-term or high-dose consumption is potentially harmful. Case Report: The case of a 43-year-old man, with a complaint of urinary stream interruption, dysuria, and flank pain, following a non-prescribed use of ginger was reported. The symptoms were reported to persist for four years, despite some medical referrals. Remarkably, the symptoms were attested to be shrinking eight weeks after ginger-intake cessation; besides, no further intervention was asserted. Conclusion: The history of herbal remedies use should be considered in patients with any unexplained urinary symptoms. [GMJ.2018;7:e1086]